Dysregulation and chronicity of pathogenic T cell responses in the pre-diseased stage of lupus - Ohmes, Justus; Comdühr, Sara; Akbarzadeh, Reza; Riemekasten, Gabriela; Humrich, Jens Y. (Frontiers in Immunology, 2022)
In the normal immune system, T cell activation is tightly regulated and controlled at several levels to ensure that activation occurs in the right context to prevent the development of pathologic conditions such as autoimmunity or other harmful immune responses. CD4+FoxP3+ regulatory T cells (Treg) are crucial for the regulation of T cell responses in the peripheral lymphatic organs and thus for the prevention and control of autoimmunity. In systemic lupus erythematosus (SLE), a prototypic systemic autoimmune disease with complex etiology, a disbalance between Treg and pathogenic effector/memory CD4+ T cells develops during disease progression indicating that gradual loss of control over T cell activation is an important event in the immune pathogenesis. This progressive failure to adequately regulate the activation of autoreactive T cells facilitates chronic activation and effector/memory differentiation of pathogenic T cells, which are considered to contribute significantly to the induction and perpetuation of autoimmune processes and tissue inflammation in SLE. However, in particular in humans, little is known about the factors which drive the escape from immune regulation and the chronicity of pathogenic T cell responses in an early stage of autoimmune disease when clinical symptoms are still unapparent. Here we briefly summarize important findings and discuss current views and models on the mechanisms related to the dysregulation of T cell responses which promotes chronicity and pathogenic memory differentiation with a focus on the early stage of disease in lupus-prone individuals.